Finite Element Analysis and Investigation of Critical Impact Point of Steel Guardrails Affecting Safety and Structural Performance - Ozcanan, Sedat (Turkish Chamber Civil Engineers, 2023)
After the guardrails are designed, the structural adequacy and safety criteria are determined by the relevant standards and full-scale crash tests. One of the widely used standards is European Norm 1317 (EN1317). Guardrail systems generally consist of rails and posts. The guardrails are more rigid around the posts, which are mounted on the ground or embedded in soil at certain intervals. Therefore, it is important for driver/passenger and roadside safety to determine the most critical point in terms of structural and safety performance and design according to the most unfavourable situation. With this motivation, in this study, the effect of different impact points on the structural and safety performance of the H1W4 guardrail was investigated by finite element (FE) analysis. For this purpose, first of all, the finite element models of the H1W4-A system were calibrated and validated with real crash test data. Then, with the help of the validated models, analyses were completed for different impact points as 0.5, 1.0, 1.5 and 2.0 meters with a half-meter difference for the standard 2 -meter post spacing. In the light of the measured safety parameters such as Acceleration Severity Index (ASI), Theoretical Head Impact Velocity (THIV) and structural performance criteria such as working width (W) and exit angle (alpha), the critical impact point for the guardrail was determined. Contrary to what is generally known, crashing vehicles into flexible points (0.5 and 1.0 m) rather than impacting rigid points (1.5 and 2.0 m) creates a more negative situation in crash tests.
Keywords: Guardrail; EN1317; ASI; THIV; finite element analysis